Hippocampal CA1 replay becomes less prominent but more rigid without inputs from medial entorhinal cortex - Chenani, Alireza; Schlesiger, Magdalene (Nature Communications, 2019)
Medial entorhinal cortex (MEC) is involved in memory processes that entail the replay of sequential firing of hippocampal place cells during rest periods and during behaviour. Here, the authors show that MEC lesioned animals show intact replay after an epoch of rats running on a linear track, while replay during the behavioral epoch is reduced.